2020
DOI: 10.1017/s0033291720003396
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between jumping to conclusions and clinical outcomes in people at clinical high-risk for psychosis

Abstract: Background Psychosis is associated with a reasoning bias, which manifests as a tendency to ‘jump to conclusions’. We examined this bias in people at clinical high-risk for psychosis (CHR) and investigated its relationship with their clinical outcomes. Methods In total, 303 CHR subjects and 57 healthy controls (HC) were included. Both groups were assessed at baseline, and after 1 and 2 years. A ‘beads’ task was used to assess reasoning bias. Symptoms and level of functioning were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…22,45 Generally, CHR participants show altered uncertainty processing as measured by salience tasks 39 which are associated with transition to psychosis. 46 In CHR participants not taking antipsychotic medication at baseline, we replicated the association between hearing SIs with uncertain valence and non-remission, and we also observed an association between hearing SIs with uncertain valence and transition to psychosis. This latter result is in line with a previous study that reported that the perceived length of SIs in multispeaker babble was associated with transition to psychosis in CHR participants, 23 but only in medication-free participants.…”
Section: Discussionsupporting
confidence: 74%
“…22,45 Generally, CHR participants show altered uncertainty processing as measured by salience tasks 39 which are associated with transition to psychosis. 46 In CHR participants not taking antipsychotic medication at baseline, we replicated the association between hearing SIs with uncertain valence and non-remission, and we also observed an association between hearing SIs with uncertain valence and transition to psychosis. This latter result is in line with a previous study that reported that the perceived length of SIs in multispeaker babble was associated with transition to psychosis in CHR participants, 23 but only in medication-free participants.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, psychosis is associated with jumping to conclusions, whereby those with psychosis are more likely to update their beliefs using less information [e.g., ( 111 , 112 )]. A study in those at risk suggested that this reasoning bias develops with the onset of psychosis and may not be evident beforehand ( 113 ). Decreased activation of the nucleus accumbens, anterior cingulate cortex, and dorsolateral PFC has been associated with impaired reward learning in those with schizophrenia ( 90 , 114 ).…”
Section: Reward Processing In Psychosismentioning
confidence: 99%
“…We tested the three research questions with linear mixed-effects models including probability estimates as dependent variable and education, medication, sex, and study as covariates. JTC was defined as reaching a decision after fish 35 and low and high current delusions were defined based on a median split of the Psychotic Symptom Rating Scales (PSYRATS) 36 : Delusion subscale. Additionally, we assessed trial-by-trial behavior with nonparametric Kruskal–Wallis tests Bonferroni-corrected for the number of trials ( n = 10).…”
Section: Methodsmentioning
confidence: 99%